Longitudinal 18F-FDG PET and MRI Reveal Evolving Imaging Pathology That Corresponds to Disease Progression in a Patient With ALS-FTD - Rajagopalan, Venkateswaran; Pioro, Erik P. (Frontiers in Neurology, 2019)
Single time point positron emission tomography (PET) studies of patients with amyotrophic lateral sclerosis and frontotemporal dementia (ALS-FTD), have demonstrated hypometabolism or hypermetabolism in certain brain regions. To determine whether longitudinal (at baseline and 20.4 months later) PET and magnetic resonance imaging (MRI) measures reveal evolving brain imaging pathology corresponding to clinical progression in a patient with ALS-FTD, cerebral glucose metabolic rate, cortical thickness (CT) and cortical area (CA) were obtained and symmetric percent change (SPC) for each calculated. The patient had worsening symptoms and signs of bulbar-onset upper motor neuron-predominant ALS as well as language and behavioral dysfunction. At baseline, minimally decreased ALSFRS-R (42/48) reflecting bulbar dysfunction was observed, along with language and executive function difficulties. At follow-up, bulbar and limb function rapidly declined as revealed by lower ALSFRS-R (27/48) and worsening language and cognitive function. PET revealed either hyper- and hypo-metabolic changes in several brain regions, especially in the left hemisphere. Marked clinical decline was accompanied by worsening cerebral and subcortical hyper and hypo-metabolism along with CT changes in regions known to degenerate in the primary progressive aphasia (PPA) form of ALS-FTD. Our case report demonstrates for the first time the progressive functional and structural neuroimaging abnormalities underlying clinical motor and neurocognitive deficits evolving in a patient with bulbar-onset ALS-FTD. Correlating neurological and neurocognitive decline with PET and MRI neuroimaging measures can provide better insights into pathophysiological mechanisms of ALS and ALS-FTD.